1979
DOI: 10.1093/brain/102.2.405
|View full text |Cite
|
Sign up to set email alerts
|

Different Types of Disturbed Motor Control in Gait of Hemiparetic Patients

Abstract: The pattern of muscle activation in walking was studied in a group of 26 hemiparetic patients. Electromyograms were taken with surface electrodes from 6 muscle groups of the paretic leg and analysed after rectification and time averaging. The sagittal rotations in hip, knee and ankle joint were determined with intermittent light photography. The muscle activation pattern of each patient was compared to that in healthy subjects as well as to the movements performed by the patient and to the normal movement patt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
229
3
14

Year Published

1981
1981
2011
2011

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 453 publications
(275 citation statements)
references
References 0 publications
18
229
3
14
Order By: Relevance
“…Despite this effort to regain optimal walking function, only a small percentage (18%-25%) attain a walking speed that is required for community activities. [2][3][4] Possible factors contributing to their difficulties with gait include muscle weakness, [5][6][7] abnormal muscle activation patterns, 8 disturbed sensation, impaired postural control, disturbed cognition, and neglect.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this effort to regain optimal walking function, only a small percentage (18%-25%) attain a walking speed that is required for community activities. [2][3][4] Possible factors contributing to their difficulties with gait include muscle weakness, [5][6][7] abnormal muscle activation patterns, 8 disturbed sensation, impaired postural control, disturbed cognition, and neglect.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have suggested classification of different types of hemiplegic gait patterns in stroke patients. [11][12][13][14] However, much is still unknown about the relation between the changes in gait patterns over time and functional recovery of walking ability in stroke patients. Our purpose in this study, therefore, was to gain more insight into this relation.…”
mentioning
confidence: 99%
“…Burdett et al (1988) found certain leg joint angle values at certain gait phases to be most important qualitative traits distinguishing gait in post stroke patients from that of ablebodied subjects. Other authors concluded that the greatest differences between pathological and normal gait involve the maximal and minimal angles in the knee and ankle joints during the toe-off stage and at first foot contact with the ground (Knutsson & Richards 1979, Intiso et al, 1996. With respect to post stroke patients, in particular, impressive classification results (98%) were obtained by Mulroy et al (2003), utilizing the maximal and minimal values of only three kinematic parameters.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of post stroke dysfunction, numerous authors (Mulroy et al, 2003;Knutsson & Richards, 1979;Perry et al, 1995;Kramers de Quervain et al, 1996;Kinsella & Moran, 2008) have attempted to identify homogeneous subgroups of post stroke walking patterns. Knutsson & Richards (1979) used EMG signals to distinguish three types of pathological gait. Kramers de Quervain et al (1995) used the Mahalanobis distance statistical technique on five temporal distance parameters to distinguish four gait patterns.…”
mentioning
confidence: 99%